S-(1,3-Dioxoisoindolin-2-yl)O,O‑diethyl phosphorothioate (SDDP): A practical electrophilic reagent for the phosphorothiolation of electron-rich compounds - Ma, Ze-Yuan; Xiao, Mei; Li, Cheng-Kun; Shoberu, Adedamola; Zou, Jian-Ping (Chinese chemical letters, 2024)
An efficient synthesis of the electrophilic reagent, S-(1,3-dioxoisoindolin-2-yl)O,O‑diethyl phosphorothioate (SDDP) is described. Moreover, the synthetic applications of SDDP wherein the transfer of the SP(O)(OEt)2 moiety occurs were investigated. In this manner, SDDP underwent facile SP(O)(OEt)2 transfer with electron-rich substrates such as ketones, indoles, and thiols to form α-phosphorothiolated ketones, 3-phosphorothiolated indoles and S-phosphorothiolated thioethers, respectively. An efficient synthesis of the electrophilic reagent, S-(1,3-dioxoisoindolin-2-yl) O,O‑diethyl phosphorothioate (SDDP) is described. Moreover, the synthetic applications of SDDP wherein the transfer of the SP(O)(OEt)2 moiety occurs were investigated. In this manner, SDDP underwent facile SP(O)(OEt)2 transfer with electron-rich substrates such as ketones, indoles, and thiols to form ɑ-phosphorothiolated ketones, 3-phosph. [Display omitted]